2005
DOI: 10.1529/biophysj.105.067694
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Reassessment of Penetratin Translocation Across Lipid Membranes

Abstract: Penetratin is a short, basic cell-penetrating peptide able to induce cellular uptake of a vast variety of large, hydrophilic cargos. We have reassessed the highly controversial issue of direct permeation of the strongly cationic peptide across negatively charged lipid membranes. Confocal laser scanning microscopy on rhodamine-labeled giant vesicles incubated with carboxyfluorescein-labeled penetratin yielded no evidence of transbilayer movement, in contradiction to previously reported results. Confocal fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Recent evidence suggests a role for transbilayer potential in peptide translocation, [25,28,29] although there is debate on this point. [30] Silvius and co-workers showed that the cationic peptide penetratin could cross synthetic phospholipid membranes in the presence of a membrane potential, [28] while similar results were reported by Graslund and colleagues [29] in experiments designed to model the endosomal escape of penetratin. In the absence of a membrane potential, little or no peptide translocation was observed.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recent evidence suggests a role for transbilayer potential in peptide translocation, [25,28,29] although there is debate on this point. [30] Silvius and co-workers showed that the cationic peptide penetratin could cross synthetic phospholipid membranes in the presence of a membrane potential, [28] while similar results were reported by Graslund and colleagues [29] in experiments designed to model the endosomal escape of penetratin. In the absence of a membrane potential, little or no peptide translocation was observed.…”
Section: Introductionmentioning
confidence: 63%
“…However, Bµrµny-Wallje et al were unable to detect movement of penetratin across synthetic bilayers in the presence or absence of a potential. [30] Wender et al reported a role for membrane potential in the entry of arginine oligomers into living cells. [25] We have exploited unique features of b-amino acid oligo-A C H T U N G T R E N N U N G mers ("b-peptides") to explore the effects of molecular shape stability and of the geometry of guanidinium group display on the entry of cationic peptides into mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, recent reports excluding endocytosis as an uptake mechanism do not appear convincing. [79] Since passive membrane diffusion of peptides has long been known as impossible, [80,81] what else can possibly be offered as a transport mechanism? Transient water wires across a lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…CPPs are linear sequences ranging between 10 and 30 amino acids that contain positively charged residues (tryptophan, arginine, or phenylalanine). Peptide uptake is enhanced by the interaction of positively charged residues with negatively charged membranes, resulting in endocytosis (3). In contrast with CPPs, the P. yoelii peptides tested here contain a single tryptophan with an isoelectric point (pI) of 3.96.…”
Section: Discussionmentioning
confidence: 99%